Cross-site scripting attack detection based on a modified convolution neural network - Yan, Huyong; Feng, Li; Yu, You; Liao, Weiling; Feng, Lei; Zhang, Jingyue; Liu, Dan; Zou, Ying; Liu, Chongwen; Qu, Linfa; Zhang, Xiaoman (Frontiers in Computational Neuroscience, 2022)
Cross-site scripting (XSS) attacks are currently one of the most threatening network attack methods. Effectively detecting and intercepting XSS attacks is an important research topic in the field of network security. This paper proposes a convolutional neural network based on a modified ResNet block and NiN model (MRBN-CNN) to tackle this problem. The main innovations of this model are to preprocess the URL according to the syntax and semantic characteristics of XSS attack script encoding, improve the ResNet residual module, extract features from three different angles, and replace the full connection layer in combination with the 1*1 convolution characteristics. Compared with the traditional machine learning and deep learning detection models, it is found that this model has better performance and convergence time. In addition, the proposed method has a detection rate compared to a baseline of approximately 75% of up to 99.23% accuracy, 99.94 precision, and a 98.53% recall value.